71.1k views
2 votes
-6(3-6r)=-18+4r solve

2 Answers

5 votes

Answer:

r = 0

Explanation:

-6(3 - 6r) = -18 + 4r //Distribute -6

-18 + 36r = -18 + 4r // Add 18 on both sides

36r = 4r //Subtract 4r on both sides

36r - 4r = 0 //Combine like terms

32r = 0 //Divide 32 on both sides

r = 0/32

r = 0

Check:

-6(3 -6r) = -18 + 4r //Replace 0 in place of r, since r=0

-6(3 - 6(0)) = -18 + 4(0) //Multiple

-6(3) = -18

-18 = -18 //True, therefore r=0

User MoonshineOutlaw
by
4.2k points
7 votes

Answer:

r = 0

Explanation:

-6 (3 - 6r) = -18 + 4r

-18 + 36r = -18 + 4r

-18 (+18) + 36r = -18 (+18) + 4r

36r = 0 + 4r (-4r)

(-4r) + 36r = 32r

32r = 0

0/32 = 0

User Youssif Saeed
by
6.3k points